1969
DOI: 10.1063/1.1664979
|View full text |Cite
|
Sign up to set email alerts
|

On Next-Nearest-Neighbor Interaction in Linear Chain. II

Abstract: Continuing our work on the ground-state properties of the Hamiltonian H=12J ∑ i=1N σi·σi+1 + 12Jα ∑ i=1N σi·σi+2, −1≤α≤1,we have completed the study of 10 spins. The results of short-chain calculations provide better upper and lower bounds of the ground-state energy per particle as N → ∞, but no simple formula can be fitted to the data to get this limit for all α. For J > 0 and α = ½, however, this is exactly found to be −¾J. Some upper and lower bounds for the free energy are also derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
250
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(257 citation statements)
references
References 7 publications
6
250
0
1
Order By: Relevance
“…This is the case with MajumdarGhosh [34,35] model [20]. Here we will see a similar phenomena, where the matrix product state is the sum of many ground states each of which breaks the translation symmetry of the original Hamiltonian.…”
Section: Introductionsupporting
confidence: 53%
“…This is the case with MajumdarGhosh [34,35] model [20]. Here we will see a similar phenomena, where the matrix product state is the sum of many ground states each of which breaks the translation symmetry of the original Hamiltonian.…”
Section: Introductionsupporting
confidence: 53%
“…7,8) These studies have revealed that the system undergoes a phase transition from the spin-liquid phase to the dimer phase at j = j c (∆) with increasing j.…”
mentioning
confidence: 99%
“…In the gapped regime, the Lieb-Schultz-Mattis theorem [25] guarantees that the ground state is degenerate. Another possible generalization is the inclusion of local, but not "nearest neighbor," couplings (so-called "Majumdar-Ghosh" couplings [26]) of the form These couplings can dramatically change the behavior of the chain in the thermodynamic limit. For example, the AF spin-1 2 chain becomes gapped when J 2 = 1 2 J 1 and all other J k vanish [26].…”
Section: The Heisenberg Spin-1 2 Chain and Its Generalizationsmentioning
confidence: 99%
“…Then, any K appearing in the fusion of I and J satisfies S AK * /S 0K * = S A0 /S 00 . 26 Proof. We have…”
Section: A Fusion Theoremmentioning
confidence: 99%